Studing of the effect of spraying with Foliartal fertilizer and Acadian organic fertilizer on some physiological characteristics of the plant Adhatoda vasica L. (Journal of the College of Basic Education, 2024)
The experiment was carried out during the 2022-2023 season, in the Department of Science / College of Basic Education / Al-Mustansiriya University, to determine the effect of Foliartal fertilizer and Acadian organic fertilizer on the the Adhatoda vasica L plant. The experiment was designed with completely randomized blocks (RCBD) and three replicates that included three concentrations of foliar fertilizer (0, 4, 8) ml/L and three concentrations of organic fertilizer (0, 1, 2) g/L. The results of treating the plants with foliar fertilizer showed a significant increase in the traits. The results showed that a concentration of 8 ml/liter of foliar fertilizer achieved the highest significant increase in plant height, number of leaves, leaf area, and total chlorophyll. The high concentration of foliar fertilizer also caused a significant increase in the plant’s substance Vasicine. Also, treating plants with organic fertilizer had a positive effect on the studied traits. Double the recommended concentration of organic fertilizer achieved a significant increase in plant height, number of leaves, leaf area, total chlorophyll, and plant substance Vasicine. The interaction between the treatments showed a significant increase in most of the studied traits in particular When combined with 8 ml/L of foliar fertilizer and twice the amount of organic fertilizer.